Optimization of fermentation conditions and blending process of fairy bean in North Anhui Province - Qishun Zhu; Jie Yang; Tingting Shen; Qi Zhang; Shoubao Yan (AMB Express)
Abstract Functional fermentation strains were isolated and screened from traditional fairy beans in northern Anhui. Through technical identification, Bacillus subtilis SXD06 was determined to be the superior fermentation strain, while Wickerhamomyces anomalus YE006 was identified as the optimal aroma-producing yeast. Utilizing single-factor experiments and response surface optimization, a Central Composite Design fermentation and blending model was established. The optimal fermentation conditions were determined to be: an inoculation amount of 1.1% for Bacillus subtilis SXD06, an inoculation amount of 4.2% for Wickerhamomyces anomalus YE006, and a fermentation temperature of 34 °C, Fermentation lasted 84.2 h. SDS-PAGE electrophoresis comparison between control and sample groups indicated effective fermentation, with most fairy beans converting to amino acids. Optimal conditions were identified as 5.5% salt, 0.26% star anise powder, 0.25% cinnamon, 1.5% pepper, 4.5% edible alcohol, and 0.28% fragrant leaves. The sensory evaluation of soybean products produced under the specified conditions yielded the highest scores. This study offers robust technical support for the development of low-ammonia, high-quality fairy bean products that align with consumer preferences. Graphical abstract